Differential expression of two Xenopus c-myc proto-oncogenes during development. - Vriz, S (1989)
Two distinct Xenopus c-myc cDNA clones have been characterized from an oocyte cDNA library. This allowed a comparison of the c-myc protein sequence across the vertebrate phylum to be made and prominent conservations to be identified. The majority of the sequence differences between the two Xenopus c-myc cDNAs are in the 5' and 3' untranslated regions. Sequence-specific oligonucleotide probes from the 5' untranslated region were used to demonstrate the differential expression of the two c-myc mRNAs during development. One of the mRNAs corresponds to the Xenopus c-myc gene previously reported expressed as a stable maternal mRNA uncoupled from cell division during oogenesis (c-myc I). It is the major mRNA species expressed during oogenesis and is expressed again from the zygotic genome in post-gastrula embryos. In contrast, the second c-myc mRNA (c-myc II) is expressed only from the maternal genome during oogenesis. Primer extension experiments show that in the oocyte the transcriptional initiation sites for c-myc I and c-myc II are at different distances from the translational start site. The 'oocyte-specific' and 'somatic-type' developmental regulation of c-myc is reminiscent of polymerase III 5S RNA gene expression in Xenopus, and may provide new insights into the developmental regulation of genes transcribed by RNA polymerase II.